Increasing Human Rights and Gender Equality (LGBTQ) through the Promotion of Local Arts and Culture with the Participation for Sustainable Development: Case Study of Students in Classical of Dramatic Arts and Performance, Faculty of Humanities and Social Sciences, Maha Sarakham Rajabhat University - Photisansuk, Sunisa; Puntura, Sakuna; Sritho, Natdanai (Chophayom Journal, 2025)
A study on Increasing Human Rights and Gender Equality (LGBTQ) through the Promotion of Local Arts and Culture with the Participation for Sustainable Development: A Case Study of Students in Classical of Dramatic Arts and Performance, Faculty of Humanities and Social Sciences, Maha Sarakham University The objectives are 1) To study the development of increasing human rights and gender equality (LGBTQ) through the promotion of local arts and culture: a case study of students in Classical of Dramatic Arts and Performance, Faculty of Humanities and Social Sciences, Maha Sarakham University And 2) To create a set of knowledge on increasing human rights and gender equality (LGBTQ) through the promotion of local arts and culture with participation for sustainable development: a case study of students Classical of Dramatic Arts and Performance, Faculty of Humanities and Social Sciences, Maha Sarakham University. The researcher reviewed documents, concepts, theories, research, interviews and fieldwork related to this study. The data collection tools were as follows: interview forms, video recording tools and other information communication tools. The research results found that 1) Promoting local arts and culture to support human rights and gender equality (LGBTQ) with community participation. It was found that the LGBTQ group is a good driving force for arts and culture. It is mostly seen in annual merit-making ceremonies such as Songkran, Boon Bang Fai, Khao Phansa, Loi Krathong, etc., with queer theory and participatory theory as a link. 2) Increasing human rights in terms of creativity in costume design for performances from the LGBTQ group to promote local arts and culture. It was found that creativity is a search for open-ended problem-solving methods, using methods that are out of the ordinary and will result in further benefits. It is a diverse, broad, multi-faceted idea that emphasizes both quantity and quality. The researcher incorporated aesthetic theory into this research. 3) Designing lyrics and melodies from the LGBTQ group to promote local arts and culture leading to sustainable development From interviews and fieldwork, it was found that the LGBTQ group was creative in choosing appropriate words and understanding the point. They will adhere to the principle of analyzing content from fieldwork or community access every time. They focus on promoting local arts and culture leading to sustainable development in the form of Soft Power by using the aesthetic theory as the core of the research and 4) Definitions regarding the creation of dance works by students in Classical of Dramatic Arts and Performance, LGBTQ group, which leads to the sustainable development and promotion of local arts and culture. From the interviews, it was found that dance, art and music have stimulating variables that are aesthetic elements and create aesthetic experiences for viewers at various levels by bringing development theory into the study this time. Keywords: Human rights, Gender equality (LGBTQ), Local arts and culture, Students in the Department